Bench-scale demonstration of CO2 capture with an electrochemically driven proton concentration process. Issue 29 (29th April 2020) - Rahimi, Mohammad; Catalini, Giulia; Puccini, Monica; Hatton, T. Alan
Abstract : A bench-scale demonstration of CO2 capture from industrial flue gas with an electrochemically driven proton concentration process was demonstrated. Abstract : A thorough experimental investigation of a bench-scale apparatus of the proton concentration process with two symmetrical MnO2 electrodes is presented, with the aim of continuous desorption of CO2 from a K2 CO3 solution. The electrodes were fabricated through cathodic deposition, and their chemical states, morphology, and microstructural architecture were characterized with X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Successful formation of MnO2 film was confirmed by XPS analysis, and the SEM images showed a uniform distribution of the film across the carbon substrate surface and along the strand, with an average thickness of ∼500 nm, thus making proton ion diffusion possible. Continuous and efficient desorption of CO2 from a K2 CO3 solution was obtained when electrodeposited MnO2 electrodes were used in a flow-based proton concentration process. The amount of CO2 desorbed per area of the electrode was 12-fold higher than that of a similar system. The electrochemical nature of the proton concentration process offers substantial practical advantages for the future, especially if electricity can be sustainably produced from renewable sources.